OSVITOLOGICAL CHARACTERISTICS OF FORMATION FACTORS PSYCHOLOGICAL COMPONENT IN TRAINING FUTURE SPECIALISTS - Savrasova-V’un Tatiana А. (Educological discourse, 2016)
The article presents the factors that influence the formation of the psychological component in the training of future specialists. Characterized essence of the psychological component of professional competence of future specialists. When covering the position of scientists to determine the factors of formation of psychological components of the professional training of future specialists. Identify and analyze the content of the main factors of the formation of the psychological component in the training of future specialists.